2022
DOI: 10.1039/d2gc01092e
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable synthesis of bio-based PTMEG and methane beyond the Reppe method

Abstract: To resolve the issues of a highly polluting and energy-intensive industry based on the Reppe method, herein we developed an economically feasible green route for the synthesis of poly(tetramethylene ether...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…1). Zhao et al recently reported that PTMG could be synthesized from furfural as a potential biobased diol, 36 and we thus incorporated it as a soft segment to provide softness, which was important for the interfacial wettability of adhesives. The ratio of EG to PTMG was varied to adjust the structure and physiochemical properties of the PETFs.…”
Section: Resultsmentioning
confidence: 99%
“…1). Zhao et al recently reported that PTMG could be synthesized from furfural as a potential biobased diol, 36 and we thus incorporated it as a soft segment to provide softness, which was important for the interfacial wettability of adhesives. The ratio of EG to PTMG was varied to adjust the structure and physiochemical properties of the PETFs.…”
Section: Resultsmentioning
confidence: 99%
“…HMF is chemisorbed on the Pd surface in a flat-lying adsorption configuration over the parent Pd/C and FPhS–Pd/C, with both unsaturated furan and CO peaks red-shifted from 1030 and 1665 cm –1 to 970 and 1642 cm –1 , respectively, but the peak of saturated C–OH remains unchanged. , After H 2 –H 2 O activation, Pd/C still shows a flat-lying adsorption configuration, which matches with their observed catalytic overhydrogenation route. In contrast, FPhS–Pd/C shows a vertical adsorption configuration as indexed by the red shift of the C–OH peaks from 3422 to 3378 cm –1 and the unchanged furan and CO peaks. , It is apparent that Brønsted acidic H + prefers to attach the C–OH group via hydrogen-bonding interactions and simultaneously hinders the CO or furan-ring group from approaching the metal surface. To further distinguish the adsorption mode of CO and C–OH, an adsorption experiment of mixed MF and MFA was conducted (Figure S26).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, FPhS−Pd/C shows a vertical adsorption configuration as indexed by the red shift of the C−OH peaks from 3422 to 3378 cm −1 and the unchanged furan and C�O peaks. 63,64 It is apparent that Brønsted acidic H + prefers to attach the C−OH group via hydrogen-bonding interactions and simultaneously hinders the C�O or furanring group from approaching the metal surface. To further distinguish the adsorption mode of C�O and C−OH, an adsorption experiment of mixed MF and MFA was conducted (Figure S26).…”
Section: ■ Materials and Methodsmentioning
confidence: 91%
“…New route for the hydrogenation and decarbonylation of FA to synthesize bio-based THF. In order to solve the problems of severe carbon accumulation and deactivation and leaching of noble metal Pd and Pt catalysts during the decarbonylation of FA, Zhao et al 123 developed a novel and economically feasible green route for the synthesis of THF and thus for the corresponding PTMEG (Fig. 7).…”
Section: Bio-based 14-bdo and Thf Synthesismentioning
confidence: 99%